Síntese e caracterização de complexos metálicos de antimônio, bismuto e estanho com lapachol - Meiriane Mariano da Silva (2009)
Lapachol is a natural naphthoquinone with broad spectrum of biological activities, including antitumor, antileishmania, antiviral, analgesic, antifungal properties. Because of its antitumor property, changes in the structure of lapachol have been made such as to reduce its side effects without affecting its effectiveness. One option is to use the lapachol as ligand in coordination compounds. The lapachol was found to form 1:1 complexes with antimony(V), bismuth(V) and tin(IV), hypothesis confirmed by elemental analysis. Characterization of the complexes by infrared and ¹H and ¹³C NMR spectroscopies revealed that the coordination occurs through the formation of a chelate ring with the lapachol keto-enol oxygens. UV-Vis absoption, molar conductivity, thermogravimetry and mass spectrometry with electrospray ionization were also used to characterize the complexes. The three compounds synthesized, when added to a medium containing leukemia tumor cells, inhibited the cell growth, indicating an antitumor activity against this cell type. The complexation of lapachol to bismuth produced a compound about 2.4 times as effective as non-complexed lapachol. On the other hand, Sb- and Sn-lapachol complexes exhibited similar activities when compared to the metal salts used in the synthesis and no improvement was observed when compared to lapachol.